2001
DOI: 10.1002/yea.694
|View full text |Cite
|
Sign up to set email alerts
|

In situlocalization of β‐glucans in the cell wall ofSchizosaccharomyces pombe

Abstract: The chemical composition of the cell wall of Sz. pombe is known as b-1,3-glucan, b-1,6-glucan, a-1,3-glucan and a-galactomannan; however, the three-dimensional interactions of those macromolecules have not yet been clarified. Transmission electron microscopy reveals a three-layered structure: the outer layer is electron-dense, the adjacent layer is less dense, and the third layer bordering the cell membrane is dense. In intact cells of Sz. pombe, the high-resolution scanning electron microscope reveals a surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
154
0
24

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(183 citation statements)
references
References 28 publications
5
154
0
24
Order By: Relevance
“…In comparison, the ␤-(1,6)-glucan molecule that we characterized has a slightly higher DP than the one isolated earlier by Manners et al . 4 The unique recombinant endo-␤-(1,6)-glucanase from T. harzianum used to date releases mainly G 2 and G 3 and some G 4 and G 5 from pustulan (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the ␤-(1,6)-glucan molecule that we characterized has a slightly higher DP than the one isolated earlier by Manners et al . 4 The unique recombinant endo-␤-(1,6)-glucanase from T. harzianum used to date releases mainly G 2 and G 3 and some G 4 and G 5 from pustulan (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact structure of the ␤-(1,6)-glucan and the mode of biosynthesis of this polymer are largely unknown. In S. pombe, immunodetection studies suggested that synthesis of this polymer backbone begins in the endoplasmic reticulum, with extension occurring in the Golgi (4) and final processing at the plasma membrane. In S. cerevisiae, Montijn and co-workers (5), by immunogold labeling, detected ␤-(1,6)-glucan at the plasma membrane, suggesting that the synthesis takes place largely at the cell surface.…”
mentioning
confidence: 99%
“…As septum biogenesis proceeds, actin reorganizes to clusters of patches on both sides of the septum (Marks and Hyams, 1985). Secondary septa are then formed on either side of the primary one that is eventually dissolved resulting in cell separation (Humbel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As septum biogenesis proceeds, actin reorganizes to clusters of patches on both sides of the septum (Marks and Hyams, 1985). Secondary septa are then formed on either side of the primary one that is eventually dissolved resulting in cell separation (Humbel et al, 2001).Formation and remodeling of the cell wall depend on action of enzymes such as the (1,3)-␤-glucan-synthase and the endo-␤-1,3-glucanase that are involved in organizing the (1,3)-␤-glucan, the major constituent of the cell wall (Ribas et al, 1991;Martin-Cuadrado et al, 2003). These proteins have been shown to localize to the sites of active growth and their localization depends on secretion (Cortes et al, 2002; MartinCuadrado et al, 2003).…”
mentioning
confidence: 99%
“…After this, each daughter builds cell wall material on its own side of the primary septum, leading to the assembly of a secondary septum. The primary septum contains mainly 1,3-b-glucan and the secondary septum contains 1,3-a-glucan, 1,6-branched 1,3-b-glucan, and galactomannans (Humbel et al 2001;Sugawara et al 2003). Recently, several enzymes involved in synthesis of 1,3-b-glucan and 1,3-a-glucan have been identified, and all of them are large integral membrane proteins.…”
mentioning
confidence: 99%